Biomechanical Insights into Ski Mountaineering: Kinematics and Muscular Activation in Uphill Movements - Lucia Donno; Carlalberto Francia; Filippo Motta; Antonella LoMauro; Carlo Gorla; Diego Scaccabarozzi; Marco Tarabini; Manuela Galli (Applied Sciences)
Ski mountaineering (Skimo) combines mountain climbing and skiing, with ascents on skis or by carrying them, followed by ski descents. Despite its popularity, the literature lacks integrated biomechanical analyses during indoor training, limiting evidence-based recommendations for training, injury prevention, and performance improvement in this sport. This study analyzed four Skimo athletes during uphill walking and running on a 9° inclined treadmill at 7 km/h and 8 km/h. Kinematics was assessed by an optoelectronic system, and surface electromyography recorded the muscular activity of twelve bilateral muscles (Erector Spinae, Rectus Abdominis, Rectus Femoris, Biceps Femoris, Tibialis Anterior, Gastrocnemius Lateralis). Rectus Femoris and Biceps Femoris co-activation supported knee stability during the load support phase, especially while running. Running at 8 km/h was the most demanding condition, with increased knee flexion throughout the task cycle. Switching from 7 to 8 km/h reduced the maximum extension and increased the maximum flexion of both hip and knee and required the Gastrocnemius’ recruitment in the swing phase. Regardless of task and speed, Rectus Abdominis and Erector Spinae played a key role in stabilizing the trunk. This study provided a biomechanical characterization of two motor gestures typical in Skimo, highlighting how task typology and velocity could influence kinematics and muscle activation.